Study on size effect of limestone-concrete composite with different joint inclination angles under uniaxial compression based on the discrete element method - Hang Liu; Mingxuan Shen; Bin Du; Jie Wang; Haiyang Chen (PLoS ONE, 2026)
This study utilized synthetic rock mass technology based on the discrete element method implemented in PFC to develop multi-scale limestone-concrete composite (LCC) models in order to examine the size effect of jointed rock-concrete composites (RCC) and assess the impact of joint distribution characteristics on the composite. The variation patterns of the strength properties, deformation characteristics, and failure features with size were analyzed using uniaxial compression tests. Additionally, the impact of the joint dip angle on the size effect of the composite was explored by altering the dip angle range. The results demonstrate that both the uniaxial compressive strength (UCS) and compressive modulus of the LCC exhibit a significant size effect. The calculated difference ratios revealed that the UCS stabilized at dimensions of 600 mm × 1200 mm, whereas the compression modulus decreases by less than 10% and gradually stabilizes. Overall, the deformation characteristics of the composite are less sensitive to size variations than its strength characteristics. During failure, the energy release in the LCC became more dispersed with increasing dimensions. The failure mode transitions from global failure to dispersed localized failure, with crack propagation and stress transfer becoming more dispersed and complex. The range of joint dip angles significantly influences the size effect of the composite. Calculations of the corresponding Δ values indicated that the size effects on UCS and compressive modulus were most pronounced at joint dip angles of 75°–80° and 30°–35°, respectively. Overall, variations in the dip angle range exerted a greater impact on the size effect of UCS than on that of the compressive modulus. These findings provide valuable reference for subsequent research on RCC and related engineering projects.